1999
DOI: 10.1093/ndt/14.2.292
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia in the patient with renal insufficiency: documenting the impact and reviewing treatment strategies

Abstract: This paper attempts to present a context in which nephrologists can re-evaluate definitions of acceptable haemoglobin levels in renal populations, and re-examine previous notions about the impact of relative and absolute anaemia on patients with progressive renal insufficiency. Also, the nephrology community needs to examine rigorously treatment strategies aimed at reversing anaemia specifically in this population. Data are presented to support the notion that anaemia is disadvantageous to the patients with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Baseline information on relevant clinical variables previously found to be associated with mortality risk in this population (Levin, 1999; Rahman & Smith, 1998) was ascertained from the patients’ medical record. These included presence of diabetes and cardiovascular disease, as well as blood pressure, albumin, potassium, creatinine, hemoglobin, and blood urea nitrogen levels.…”
Section: Methodsmentioning
confidence: 99%
“…Baseline information on relevant clinical variables previously found to be associated with mortality risk in this population (Levin, 1999; Rahman & Smith, 1998) was ascertained from the patients’ medical record. These included presence of diabetes and cardiovascular disease, as well as blood pressure, albumin, potassium, creatinine, hemoglobin, and blood urea nitrogen levels.…”
Section: Methodsmentioning
confidence: 99%
“…Small studies of adult chronic renal insufficiency (CRI) have observed that patients are not routinely identified early in their clinical courses and are not treated with adequate attention to dietary protein, anemia, hypertension, and other co-morbid events [1,2,3,4,5,6,7,8]. Recently Nissenson et al [9] reviewed a large HMO database to identify an adult population with chronic kidney disease.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the kidney senses this “mild degree of anemia” with increased erythropoietin production, this Hb of 13 g/dl is frequently “missensed” by health care professionals as “insignificant.” Anemia in patients with kidney disease is probably best defined using age‐ and sex‐matched normal levels of Hb: less than 13 g/dl in nonmenstruating females and less than 14 g/dl in males. It is illogical to use significantly lower values in patients with CRI or ESRD in view of increasing recognition that Hb below normal levels is associated with worse outcomes (3,7).…”
Section: Anemia In Crimentioning
confidence: 99%